2020
DOI: 10.9734/ca/2020/v9i330138
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Representativeness of the PARADIGM-HF Study in an Outpatient Cohort of Patients with Heart Failure, Including Chagas Disease, Treated According to Guideline-directed Medical Therapy: Prospective Study, in a Single Center in Brazil

Abstract: Background: In the PARADIGM-HF trial there was a 20% reduction in hospitalization and cardiovascular mortality in patients with heart failure (HF) and treated according to guideline-directed medical therapy. Eligibility for the use of sacubitril/valsartan in the real world has varied between 12% and 76%. There are no studies on the national scene on this eligibility. Aims: To investigate the clinical eligibility of the PARADIGM-HF trial in patients with HF in the outpatient clinic of a university… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…In a prospective observational study of 136 consecutive patients with HF in a single university-affiliated hospital center, including the HF etiologies of ICM, CCCD, and idiopathic cardiomyopathy, 617 the authors reported that up to 44% of the patients had the major criteria of exclusion of the PARADIGM-HF trial. In addition, they reported that the lower blood pressure levels, common in CCCD, could lead to underuse of some drugs in this context.…”
Section: Therapeutic Management Of Ventricular Dysfunction and Heart ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective observational study of 136 consecutive patients with HF in a single university-affiliated hospital center, including the HF etiologies of ICM, CCCD, and idiopathic cardiomyopathy, 617 the authors reported that up to 44% of the patients had the major criteria of exclusion of the PARADIGM-HF trial. In addition, they reported that the lower blood pressure levels, common in CCCD, could lead to underuse of some drugs in this context.…”
Section: Therapeutic Management Of Ventricular Dysfunction and Heart ...mentioning
confidence: 99%
“…Assim, relatou-se série de pacientes com CCDC tratados com sacubitril-valsartana em hospital de referência para essa doença no Brasil, referindo-se, após 6 meses, melhora sintomática desses indivíduos. 616 Em estudo prospectivo e observacional de 136 pacientes consecutivos com IC em único centro hospitalar universitário, incluindo as etiologias CMI, CCDC e cardiomiopatia idiopática, 617 os autores verificaram que até 44% dos pacientes desse registro unicêntrico apresentavam os principais critérios de exclusão do PARADIGM-HF. Observaram ainda que níveis pressóricos mais baixos, comuns na CCDC, poderiam ter levado à subutilização de alguns medicamentos nesse contexto.…”
Section: Sacubitril-valsartanaunclassified